Perfect ghost - Barnes, Linda (Minotaur, 2013)
Required to complete a celebrity biography on her own after the suspicious death of her charismatic partner, agoraphobic ghost writer Em Moore struggles through the job's required interviews with alluring film director Garrett Malcolm, who alludes to dark family secrets and trouble with a fellow star.